Anti-cytokine therapy in rheumatoid arthritis - Sarzi-Puttini, Piercarlo (Henry Stewart Talks, 2007)
Characteristics of rheumatoid arthritis (RA), Epidemiology, Disease pathology, Synovitis, Cytokine network, Tumor necrosis factor (TNF)-alpha, The role of TNF-alpha in rheumatoid arthritis, Disease-modifying antirheumatic drugs (DMARD), TNF antagonists, Monoclonal antibodies, Adverse events and TNF antagonists, Chemokines, B cell targeting, T cell targeting, Costimulation, The pipeline of new antirheumatic drugs for RA promises to bring new therapeutic possibilities for the future
Archived at 2018/10/28